OWNERSHIP RETENTION, KEPEMILIKAN MANAJERIAL DAN DEWAN TERHADAP KINERJA SAHAM PERUSAHAAN IPO - Maximus Leonardo Taolin Umbu Ho Ara (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
The aims of research is find the impact of ownership retention, managerial ownership, and boards on value IPO premium and underpricing. We investigate by using hand collect data 202 IPO prospectuses during 2008-2017 and using Warp PLS 5.0 to compute the data. Our finding suggest that may useful to guide investor to making informed dececions to see level of proportion of sharehold by old ownership and manajemen. When the high level of ownership retention and managerial ownership, make the value IPO premium and underpricing will be high. In the other hand duality of managerial in firms making the value will be achieved. This paper contibutes on value of IPO premium and underpricing literature since influence by ownership share on initial public offerings context of emerging markets